SISTEM MONITORING STOK TANGKI AIR MEMANFAATKAN SENSOR ULTRASONIK DAN MIKROKONTROLER ARDUINO MEGA PADA DEPOT AIR MINUM - Rian Saputra; Pipin Farida Ariyani; Noni Juliasari (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2018)
Drinking water which is a vital need for human life has been widely used in the form of Drinking Water Depot. The business of drinking water depots is one of the business alternative with relatively small cost which aims at helping the community to supply cheap, healthy and practical drinking water. Currently most of the Drinking Water Depots are still using Toren tanks for their water storage. To monitor the level of height and volume of water in the tank is still using the traditional way that is by tapping the Toren tank and dip the water hose into the bottom of tank. The measurement of the height of the water in the Toren tank is being inaccurate and less practical. This practice also allows for the errors of estimating the height and volume of water. The problem is designed a tool to monitor the height and volume of water in the tank automatically. This measuring instrument consists of Arduino Mega 2560 board as a data processing center and ultrasonic sensor HY-SRF05 to measure the water level. The application program is also designed with Desktop-based and Android as an interface to facilitate the user in monitoring the water tank. Monitoring applications with database storage make it easy for users to monitor altitude levels and water volumes in the container tank in keeping the stock of water in the tank available. The water stock in the tank will remain intact. If the water supply in the tank is running low, the application can send automatic purchase orders by email to the water supplier. This makes Depot no longer need to schedule the time of booking to supply water.